Réponses

Meilleure réponse !
2013-01-05T04:55:17+01:00

Coucou,

 

I^{2}= (2\sqrt{3} + 5)^{2}= (2\sqrt{3})^{2} +5^{2} = (2^{2})(\sqrt{3})^{2} +25                                          

                                                           

=(4*3)+25 

=12+25=...

 

rappelle : (Va)² = Va x Va =a

 

J^{2}= (2\sqrt{3} - 5)^{2}= (2\sqrt{3})^{2} -5^{2} = (2^{2})(\sqrt{3})^{2} -25

=(4*3)-25 

=12-25=...

 

Puis pour I x J, on utilise  (a - b)(a + b) = a² - b²                                                                                                                                               J*I}= (2\sqrt{3} - 5)(2\sqrt{3} +5)= (2\sqrt{3})^{2} -5^{2} = [(2)^{2}(\sqrt{3})^{2}] -25

=... 

et puis c'est comme avant

 

*=multiplié

 

Voilà :)